The champagne letters : a novel - MacIntosh, Kate (Fiction writer); Cook, Eileen (Gallery Books, 2024)
"Reims, France, 1805: Barbe-Nicole Clicquot has just lost her beloved husband but is determined to pursue their dream of creating the premier champagne house in France, now named for her new identity as a widow: Veuve Clicquot. With the Russians poised to invade, competitors fighting for her customers, and the Napoleonic court politics complicating matters she must set herself apart quickly and permanently if she, and her business, are to survive. In present day Chicago, broken from her divorce, Natalie Taylor runs away to Paris. In a book stall by the Seine, Natalie finds a collection of the Widow Clicquot's published letters and uses them as inspiration to step out of her comfort zone and create a new, empowered life for herself. But when her Parisian escape takes a shocking and unexpected turn, she's forced to make a choice. Should she accept her losses and return home, or fight for the future she's only dreamed about? What would the widow do?"--